A logic-based framework for verifying consensus algorithms - Dragoi, Cezara; Henzinger, Thomas A; Veith, Helmut; Widder, Josef; Zufferey, Damien
Fault-tolerant distributed algorithms play an important role in ensuring the reliability of many software applications. In this paper we consider distributed algorithms whose computations are organized in rounds. To verify the correctness of such algorithms, we reason about (i) properties (such as invariants) of the state, (ii) the transitions controlled by the algorithm, and (iii) the communication graph. We introduce a logic that addresses these points, and contains set comprehensions with cardinality constraints, function symbols to describe the local states of each process, and a limited form of quantifier alternation to express the verification conditions. We show its use in automating the verification of consensus algorithms. In particular, we give a semi-decision procedure for the unsatisfiability problem of the logic and identify a decidable fragment. We successfully applied our framework to verify the correctness of a variety of consensus algorithms tolerant to both benign faults (message loss, process crashes) and value faults (message corruption).

Probabilistic programming - Gordon, Andrew; Henzinger, Thomas A; Nori, Aditya; Rajamani, Sriram (Proceedings of the on Future of Software Engineering)
Probabilistic programs are usual functional or imperative programs with two added constructs: (1) the ability to draw values at random from distributions, and (2) the ability to condition values of variables in a program via observations. Models from diverse application areas such as computer vision, coding theory, cryptographic protocols, biology and reliability analysis can be written as probabilistic programs. Probabilistic inference is the problem of computing an explicit representation of the probability distribution implicitly specified by a probabilistic program. Depending on the application, the desired output from inference may vary-we may want to estimate the expected value of some function f with respect to the distribution, or the mode of the distribution, or simply a set of samples drawn from the distribution. In this paper, we describe connections this research area called \Probabilistic Programming" has with programming languages and software engineering, and this includes language design, and the static and dynamic analysis of programs. We survey current state of the art and speculate on promising directions for future research.

Evolution of a fungal pathogen towards individual versus social immunity in ants - Stock, Miriam
The co-evolution of hosts and pathogens is characterized by continuous adaptations of both parties. Pathogens of social insects need to adapt towards disease defences at two levels: 1) individual immunity of each colony member consisting of behavioural defence strategies as well as humoral and cellular immune responses and 2) social immunity that is collectively performed by all group members comprising behavioural, physiological and organisational defence strategies. To disentangle the selection pressure on pathogens by the collective versus individual level of disease defence in social insects, we performed an evolution experiment using the Argentine Ant, Linepithema humile, as a host and a mixture of the general insect pathogenic fungus Metarhizium spp. (6 strains) as a pathogen. We allowed pathogen evolution over 10 serial host passages to two different evolution host treatments: (1) only individual host immunity in a single host treatment, and (2) simultaneously acting individual and social immunity in a social host treatment, in which an exposed ant was accompanied by two untreated nestmates. Before starting the pathogen evolution experiment, the 6 Metarhizium spp. strains were characterised concerning conidiospore size killing rates in singly and socially reared ants, their competitiveness under coinfecting conditions and their influence on ant behaviour. We analysed how the ancestral atrain mixture changed in conidiospere size, killing rate and strain composition dependent on host treatment (single or social hosts) during 10 passages and found that killing rate and conidiospere size of the pathogen increased under both evolution regimes, but different depending on host treatment. Testing the evolved strain mixtures that evolved under either the single or social host treatment under both single and social current rearing conditions in a full factorial design experiment revealed that the additional collective defences in insect societies add new selection pressure for their coevolving pathogens that compromise their ability to adapt to its host at the group level. To our knowledge, this is the first study directly measuring the influence of social immunity on pathogen evolution.

On the BCS gap equation for superfluid fermionic gases - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Proceedings of the QMath12 Conference)
We present a rigorous derivation of the BCS gap equation for superfluid fermionic gases with point interactions. Our starting point is the BCS energy functional, whose minimizer we investigate in the limit when the range of the interaction potential goes to zero.

Edit propagation using geometric relationship functions - Guerrero, Paul; Jeschke, Stefan; Wimmer, Michael; Wonka, Peter (ACM Transactions on Graphics)
We propose a method for propagating edit operations in 2D vector graphics, based on geometric relationship functions. These functions quantify the geometric relationship of a point to a polygon, such as the distance to the boundary or the direction to the closest corner vertex. The level sets of the relationship functions describe points with the same relationship to a polygon. For a given query point, we first determine a set of relationships to local features, construct all level sets for these relationships, and accumulate them. The maxima of the resulting distribution are points with similar geometric relationships. We show extensions to handle mirror symmetries, and discuss the use of relationship functions as local coordinate systems. Our method can be applied, for example, to interactive floorplan editing, and it is especially useful for large layouts, where individual edits would be cumbersome. We demonstrate populating 2D layouts with tens to hundreds of objects by propagating relatively few edit operations.

Clustered planarity testing revisited - Fulek, Radoslav; Kynčl, Jan; Malinović, Igor; Pálvölgyi, Dömötör (International Symposium on Graph Drawing)
The Hanani–Tutte theorem is a classical result proved for the first time in the 1930s that characterizes planar graphs as graphs that admit a drawing in the plane in which every pair of edges not sharing a vertex cross an even number of times. We generalize this classical result to clustered graphs with two disjoint clusters, and show that a straightforward extension of our result to flat clustered graphs with three or more disjoint clusters is not possible. We also give a new and short proof for a related result by Di Battista and Frati based on the matroid intersection algorithm.

Constrained Verifiable Random Functions - Fuchsbauer, Georg (SCN 2014)
We extend the notion of verifiable random functions (VRF) to constrained VRFs, which generalize the concept of constrained pseudorandom functions, put forward by Boneh and Waters (Asiacrypt’13), and independently by Kiayias et al. (CCS’13) and Boyle et al. (PKC’14), who call them delegatable PRFs and functional PRFs, respectively. In a standard VRF the secret key sk allows one to evaluate a pseudorandom function at any point of its domain; in addition, it enables computation of a non-interactive proof that the function value was computed correctly. In a constrained VRF from the key sk one can derive constrained keys skS for subsets S of the domain, which allow computation of function values and proofs only at points in S. After formally defining constrained VRFs, we derive instantiations from the multilinear-maps-based constrained PRFs by Boneh and Waters, yielding a VRF with constrained keys for any set that can be decided by a polynomial-size circuit. Our VRFs have the same function values as the Boneh-Waters PRFs and are proved secure under the same hardness assumption, showing that verifiability comes at no cost. Constrained (functional) VRFs were stated as an open problem by Boyle et al.

Generalised interpolation by solving recursion free-horn clauses - Gupta, Ashutosh; Popeea, Corneliu; Rybalchenko, Andrey (Electronic Proceedings in Theoretical Computer Science, EPTCS)
In this paper we present INTERHORN, a solver for recursion-free Horn clauses. The main application domain of INTERHORN lies in solving interpolation problems arising in software verification. We show how a range of interpolation problems, including path, transition, nested, state/transition and well-founded interpolation can be handled directly by INTERHORN. By detailing these interpolation problems and their Horn clause representations, we hope to encourage the emergence of a common back-end interpolation interface useful for diverse verification tools.

Spatio-temporal representations of uncertainty in spiking neural networks - Savin, Cristina; Denève, Sophie
It has been long argued that, because of inherent ambiguity and noise, the brain needs to represent uncertainty in the form of probability distributions. The neural encoding of such distributions remains however highly controversial. Here we present a novel circuit model for representing multidimensional real-valued distributions using a spike based spatio-temporal code. Our model combines the computational advantages of the currently competing models for probabilistic codes and exhibits realistic neural responses along a variety of classic measures. Furthermore, the model highlights the challenges associated with interpreting neural activity in relation to behavioral uncertainty and points to alternative population-level approaches for the experimental validation of distributed representations.

Auxin on the road navigated by cellular PIN polarity - Baster, Pawel; Friml, Jiří (Auxin and Its Role in Plant Development)
The generation of asymmetry, at both cellular and tissue level, is one of the most essential capabilities of all eukaryotic organisms. It mediates basically all multicellular development ranging from embryogenesis and de novo organ formation till responses to various environmental stimuli. In plants, the awe-inspiring number of such processes is regulated by phytohormone auxin and its directional, cell-to-cell transport. The mediators of this transport, PIN auxin transporters, are asymmetrically localized at the plasma membrane, and this polar localization determines the directionality of intercellular auxin flow. Thus, auxin transport contributes crucially to the generation of local auxin gradients or maxima, which instruct given cell to change its developmental program. Here, we introduce and discuss the molecular components and cellular mechanisms regulating the generation and maintenance of cellular PIN polarity, as the general hallmarks of cell polarity in plants.

Topology-preserving watermarking of vector graphics - Huber, Stefan; Held, Martin; Meerwald, Peter; Kwitt, Roland (International Journal of Computational Geometry and Applications)
Watermarking techniques for vector graphics dislocate vertices in order to embed imperceptible, yet detectable, statistical features into the input data. The embedding process may result in a change of the topology of the input data, e.g., by introducing self-intersections, which is undesirable or even disastrous for many applications. In this paper we present a watermarking framework for two-dimensional vector graphics that employs conventional watermarking techniques but still provides the guarantee that the topology of the input data is preserved. The geometric part of this framework computes so-called maximum perturbation regions (MPR) of vertices. We propose two efficient algorithms to compute MPRs based on Voronoi diagrams and constrained triangulations. Furthermore, we present two algorithms to conditionally correct the watermarked data in order to increase the watermark embedding capacity and still guarantee topological correctness. While we focus on the watermarking of input formed by straight-line segments, one of our approaches can also be extended to circular arcs. We conclude the paper by demonstrating and analyzing the applicability of our framework in conjunction with two well-known watermarking techniques.

Bose gases, Bose-Einstein condensation, and the Bogoliubov approximation - Seiringer, Robert (Journal of Mathematical Physics)
We review recent progress towards a rigorous understanding of the Bogoliubov approximation for bosonic quantum many-body systems. We focus, in particular, on the excitation spectrum of a Bose gas in the mean-field (Hartree) limit. A list of open problems will be discussed at the end.

Introduction - Jakšić, Vojkan; Pillet, Claude; Seiringer, Robert (Journal of Mathematical Physics)

Movement templates for learning of hitting and batting - Muelling, Katharina; Kroemer, Oliver; Lampert, Christoph; Schölkopf, Bernhard (Learning Motor Skills)
Hitting and batting tasks, such as tennis forehands, ping-pong strokes, or baseball batting, depend on predictions where the ball can be intercepted and how it can properly be returned to the opponent. These predictions get more accurate over time, hence the behaviors need to be continuously modified. As a result, movement templates with a learned global shape need to be adapted during the execution so that the racket reaches a target position and velocity that will return the ball over to the other side of the net or court. It requires altering learned movements to hit a varying target with the necessary velocity at a specific instant in time. Such a task cannot be incorporated straightforwardly in most movement representations suitable for learning. For example, the standard formulation of the dynamical system based motor primitives (introduced by Ijspeert et al (2002b)) does not satisfy this property despite their flexibility which has allowed learning tasks ranging from locomotion to kendama. In order to fulfill this requirement, we reformulate the Ijspeert framework to incorporate the possibility of specifying a desired hitting point and a desired hitting velocity while maintaining all advantages of the original formulation.We show that the proposed movement template formulation works well in two scenarios, i.e., for hitting a ball on a string with a table tennis racket at a specified velocity and for returning balls launched by a ball gun successfully over the net using forehand movements.

Mutational studies on resurrected ancestral proteins reveal conservation of site-specific amino acid preferences throughout evolutionary history - Risso, Valeria; Manssour Triedo, Fadia; Delgado Delgado, Asuncion; Arco, Rocio; Barroso Deljesús, Alicia; Inglés Prieto, Álvaro; Godoy Ruiz, Raquel; Gavira, Josè; Gaucher, Eric; Ibarra Molero, Beatriz; Sánchez Ruiz, Jose (Molecular Biology and Evolution)
Local protein interactions ("molecular context" effects) dictate amino acid replacements and can be described in terms of site-specific, energetic preferences for any different amino acid. It has been recently debated whether these preferences remain approximately constant during evolution or whether, due to coevolution of sites, they change strongly. Such research highlights an unresolved and fundamental issue with far-reaching implications for phylogenetic analysis and molecular evolution modeling. Here, we take advantage of the recent availability of phenotypically supported laboratory resurrections of Precambrian thioredoxins and β-lactamases to experimentally address the change of site-specific amino acid preferences over long geological timescales. Extensive mutational analyses support the notion that evolutionary adjustment to a new amino acid may occur, but to a large extent this is insufficient to erase the primitive preference for amino acid replacements. Generally, site-specific amino acid preferences appear to remain conserved throughout evolutionary history despite local sequence divergence. We show such preference conservation to be readily understandable in molecular terms and we provide crystallographic evidence for an intriguing structural-switch mechanism: Energetic preference for an ancestral amino acid in a modern protein can be linked to reorganization upon mutation to the ancestral local structure around the mutated site. Finally, we point out that site-specific preference conservation naturally leads to one plausible evolutionary explanation for the existence of intragenic global suppressor mutations.

On the geometric ramsey number of outerplanar graphs - Cibulka, Josef; Gao, Pu; Krcál, Marek; Valla, Tomáš; Valtr, Pavel (Discrete & Computational Geometry)
We prove polynomial upper bounds of geometric Ramsey numbers of pathwidth-2 outerplanar triangulations in both convex and general cases. We also prove that the geometric Ramsey numbers of the ladder graph on 2n vertices are bounded by O(n3) and O(n10), in the convex and general case, respectively. We then apply similar methods to prove an (Formula presented.) upper bound on the Ramsey number of a path with n ordered vertices.

Partial shape matching using transformation parameter similarity - Guerrero, Paul; Auzinger, Thomas; Wimmer, Michael; Jeschke, Stefan (Computer Graphics Forum)
In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching. In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching.

An auxin-mediated shift toward growth isotropy promotes organ formation at the shoot meristem in Arabidopsis - Sassi, Massimiliano; Ali, Olivier; Boudon, Frédéric; Cloarec, Gladys; Abad, Ursula; Cellier, Coralie; Chen, Xu; Gilles, Benjamin; Milani, Pascale; Friml, Jirí; Vernoux, Teva; Godin, Christophe; et al. (Current Biology)
To control morphogenesis, molecular regulatory networks have to interfere with the mechanical properties of the individual cells of developing organs and tissues, but how this is achieved is not well known. We study this issue here in the shoot meristem of higher plants, a group of undifferentiated cells where complex changes in growth rates and directions lead to the continuous formation of new organs [1, 2]. Here, we show that the plant hormone auxin plays an important role in this process via a dual, local effect on the extracellular matrix, the cell wall, which determines cell shape. Our study reveals that auxin not only causes a limited reduction in wall stiffness but also directly interferes with wall anisotropy via the regulation of cortical microtubule dynamics. We further show that to induce growth isotropy and organ outgrowth, auxin somehow interferes with the cortical microtubule-ordering activity of a network of proteins, including AUXIN BINDING PROTEIN 1 and KATANIN 1. Numerical simulations further indicate that the induced isotropy is sufficient to amplify the effects of the relatively minor changes in wall stiffness to promote organogenesis and the establishment of new growth axes in a robust manner.

Game theoretic secure localization in wireless sensor networks - Jha, Susmit; Tripakis, Stavros; Seshia, Sanjit; Chatterjee, Krishnendu
Wireless sensor networks (WSNs) composed of low-power, low-cost sensor nodes are expected to form the backbone of future intelligent networks for a broad range of civil, industrial and military applications. These sensor nodes are often deployed through random spreading, and function in dynamic environments. Many applications of WSNs such as pollution tracking, forest fire detection, and military surveillance require knowledge of the location of constituent nodes. But the use of technologies such as GPS on all nodes is prohibitive due to power and cost constraints. So, the sensor nodes need to autonomously determine their locations. Most localization techniques use anchor nodes with known locations to determine the position of remaining nodes. Localization techniques have two conflicting requirements. On one hand, an ideal localization technique should be computationally simple and on the other hand, it must be resistant to attacks that compromise anchor nodes. In this paper, we propose a computationally light-weight game theoretic secure localization technique and demonstrate its effectiveness in comparison to existing techniques.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

Suraq - a controller synthesis tool using uninterpreted functions - Hofferek, Georg; Gupta, Ashutosh (HVC 2014)
Boolean controllers for systems with complex datapaths are often very difficult to implement correctly, in particular when concurrency is involved. Yet, in many instances it is easy to formally specify correctness. For example, the specification for the controller of a pipelined processor only has to state that the pipelined processor gives the same results as a non-pipelined reference design. This makes such controllers a good target for automated synthesis. However, an efficient abstraction for the complex datapath elements is needed, as a bit-precise description is often infeasible. We present Suraq, the first controller synthesis tool which uses uninterpreted functions for the abstraction. Quantified firstorder formulas (with specific quantifier structure) serve as the specification language from which Suraq synthesizes Boolean controllers. Suraq transforms the specification into an unsatisfiable SMT formula, and uses Craig interpolation to compute its results. Using Suraq, we were able to synthesize a controller (consisting of two Boolean signals) for a five-stage pipelined DLX processor in roughly one hour and 15 minutes.

Extensional crisis and proving identity - Gupta, Ashutosh; Kovács, Laura; Kragl, Bernhard; Voronkov, Andrei (ATVA 2014)
Extensionality axioms are common when reasoning about data collections, such as arrays and functions in program analysis, or sets in mathematics. An extensionality axiom asserts that two collections are equal if they consist of the same elements at the same indices. Using extensionality is often required to show that two collections are equal. A typical example is the set theory theorem (∀x)(∀y)x∪y = y ∪x. Interestingly, while humans have no problem with proving such set identities using extensionality, they are very hard for superposition theorem provers because of the calculi they use. In this paper we show how addition of a new inference rule, called extensionality resolution, allows first-order theorem provers to easily solve problems no modern first-order theorem prover can solve. We illustrate this by running the VAMPIRE theorem prover with extensionality resolution on a number of set theory and array problems. Extensionality resolution helps VAMPIRE to solve problems from the TPTP library of first-order problems that were never solved before by any prover.

Lipschitz robustness of finite-state transducers - Henzinger, Thomas A; Otop, Jan; Samanta, Roopsha (Leibniz International Proceedings in Informatics, LIPIcs)
We investigate the problem of checking if a finite-state transducer is robust to uncertainty in its input. Our notion of robustness is based on the analytic notion of Lipschitz continuity - a transducer is K-(Lipschitz) robust if the perturbation in its output is at most K times the perturbation in its input. We quantify input and output perturbation using similarity functions. We show that K-robustness is undecidable even for deterministic transducers. We identify a class of functional transducers, which admits a polynomial time automata-theoretic decision procedure for K-robustness. This class includes Mealy machines and functional letter-to-letter transducers. We also study K-robustness of nondeterministic transducers. Since a nondeterministic transducer generates a set of output words for each input word, we quantify output perturbation using setsimilarity functions. We show that K-robustness of nondeterministic transducers is undecidable, even for letter-to-letter transducers. We identify a class of set-similarity functions which admit decidable K-robustness of letter-to-letter transducers.

Cost-aware automatic program repair - Samanta, Roopsha; Olivo, Oswaldo; Allen, Emerson
We present a formal framework for repairing infinite-state, imperative, sequential programs, with (possibly recursive) procedures and multiple assertions; the framework can generate repaired programs by modifying the original erroneous program in multiple program locations, and can ensure the readability of the repaired program using user-defined expression templates; the framework also generates a set of inductive assertions that serve as a proof of correctness of the repaired program. As a step toward integrating programmer intent and intuition in automated program repair, we present a cost-aware formulation - given a cost function associated with permissible statement modifications, the goal is to ensure that the total program modification cost does not exceed a given repair budget. As part of our predicate abstractionbased solution framework, we present a sound and complete algorithm for repair of Boolean programs. We have developed a prototype tool based on SMT solving and used it successfully to repair diverse errors in benchmark C programs.

Functionals on triangulations of delaunay sets - Dolbilin, Nikolai; Edelsbrunner, Herbert; Glazyrin, Alexey; Musin, Oleg (Moscow Mathematical Journal)
We study densities of functionals over uniformly bounded triangulations of a Delaunay set of vertices, and prove that the minimum is attained for the Delaunay triangulation if this is the case for finite sets.

Physiology: Relax and come in - Sixt, Michael K; Vaahtomeri, Kari (Nature)
During inflammation, lymph nodes swell with an influx of immune cells. New findings identify a signalling pathway that induces relaxation in the contractile cells that give structure to these organs.

Variance predicts salience in central sensory processing - Hermundstad, Ann; Briguglio, John; Conte, Mary; Victor, Jonathan; Balasubramanian, Vijay; Tkacik, Gasper (eLife)
Information processing in the sensory periphery is shaped by natural stimulus statistics. In the periphery, a transmission bottleneck constrains performance; thus efficient coding implies that natural signal components with a predictably wider range should be compressed. In a different regime—when sampling limitations constrain performance—efficient coding implies that more resources should be allocated to informative features that are more variable. We propose that this regime is relevant for sensory cortex when it extracts complex features from limited numbers of sensory samples. To test this prediction, we use central visual processing as a model: we show that visual sensitivity for local multi-point spatial correlations, described by dozens of independently-measured parameters, can be quantitatively predicted from the structure of natural images. This suggests that efficient coding applies centrally, where it extends to higher-order sensory features and operates in a regime in which sensitivity increases with feature variability.

Sequential effects in continued visual search: Using fixation-related potentials to compare distractor processing before and after target detection - Körner, Christof; Braunstein, Verena; Stangl, Matthias; Schlögl, Alois; Neuper, Christa; Ischebeck, Anja (Psychophysiology)
To search for a target in a complex environment is an everyday behavior that ends with finding the target. When we search for two identical targets, however, we must continue the search after finding the first target and memorize its location. We used fixation-related potentials to investigate the neural correlates of different stages of the search, that is, before and after finding the first target. Having found the first target influenced subsequent distractor processing. Compared to distractor fixations before the first target fixation, a negative shift was observed for three subsequent distractor fixations. These results suggest that processing a target in continued search modulates the brain's response, either transiently by reflecting temporary working memory processes or permanently by reflecting working memory retention.

Theoretical tests of the mechanical protection strategy in protein nanomechanics - Chwastyk, Mateusz; Galera Prat, Albert; Sikora, Mateusz K; Gómez Sicilia, Àngel; Carrión Vázquez, Mariano; Cieplak, Marek (Proteins: Structure, Function and Bioinformatics)
We provide theoretical tests of a novel experimental technique to determine mechanostability of proteins based on stretching a mechanically protected protein by single-molecule force spectroscopy. This technique involves stretching a homogeneous or heterogeneous chain of reference proteins (single-molecule markers) in which one of them acts as host to the guest protein under study. The guest protein is grafted into the host through genetic engineering. It is expected that unraveling of the host precedes the unraveling of the guest removing ambiguities in the reading of the force-extension patterns of the guest protein. We study examples of such systems within a coarse-grained structure-based model. We consider systems with various ratios of mechanostability for the host and guest molecules and compare them to experimental results involving cohesin I as the guest molecule. For a comparison, we also study the force-displacement patterns in proteins that are linked in a serial fashion. We find that the mechanostability of the guest is similar to that of the isolated or serially linked protein. We also demonstrate that the ideal configuration of this strategy would be one in which the host is much more mechanostable than the single-molecule markers. We finally show that it is troublesome to use the highly stable cystine knot proteins as a host to graft a guest in stretching studies because this would involve a cleaving procedure.

Novel putative driver gene mutations in chronic lymphocytic leukemia (CLL): results from a combined analysis of whole exome sequencing of 262 primary CLL aamples - Landau, Dan; Stewart, Chip; Reiter, Johannes; Lawrence, Michael; Sougnez, Carrie; Brown, Jennifer; Lopez Guillermo, Armando; Gabriel, Stacey; Lander, Eric; Neuberg, Donna; López Otín, Carlos; Campo, Elias; et al. (Blood)
Unbiased high-throughput massively parallel sequencing methods have transformed the process of discovery of novel putative driver gene mutations in cancer. In chronic lymphocytic leukemia (CLL), these methods have yielded several unexpected findings, including the driver genes SF3B1, NOTCH1 and POT1. Recent analysis, utilizing down-sampling of existing datasets, has shown that the discovery process of putative drivers is far from complete across cancer. In CLL, while driver gene mutations affecting >10% of patients were efficiently discovered with previously published CLL cohorts of up to 160 samples subjected to whole exome sequencing (WES), this sample size has only 0.78 power to detect drivers affecting 5% of patients, and only 0.12 power for drivers affecting 2% of patients. These calculations emphasize the need to apply unbiased WES to larger patient cohorts.

Translation-invariant quasi-free states for fermionic systems and the BCS approximation - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Reviews in Mathematical Physics)
We study translation-invariant quasi-free states for a system of fermions with two-particle interactions. The associated energy functional is similar to the BCS functional but also includes direct and exchange energies. We show that for suitable short-range interactions, these latter terms only lead to a renormalization of the chemical potential, with the usual properties of the BCS functional left unchanged. Our analysis thus represents a rigorous justification of part of the BCS approximation. We give bounds on the critical temperature below which the system displays superfluidity.

Functional and bioinformatics analysis of two Campylobacter jejuni homologs of the thiol-disulfide oxidoreductase, DsbA - Grabowska, Anna; Wywiał, Ewa; Dunin Horkawicz, Stanislaw; Łasica, Anna; Wösten, Marc; Nagy-Staron, Anna A; Godlewska, Renata; Bocian Ostrzycka, Katarzyna; Pieńkowska, Katarzyna; Łaniewski, Paweł; Bujnicki, Janusz; Van Putten, Jos; et al. (PLoS One)
Background: Bacterial Dsb enzymes are involved in the oxidative folding of many proteins, through the formation of disulfide bonds between their cysteine residues. The Dsb protein network has been well characterized in cells of the model microorganism Escherichia coli. To gain insight into the functioning of the Dsb system in epsilon-Proteobacteria, where it plays an important role in the colonization process, we studied two homologs of the main Escherichia coli Dsb oxidase (EcDsbA) that are present in the cells of the enteric pathogen Campylobacter jejuni, the most frequently reported bacterial cause of human enteritis in the world. Methods and Results: Phylogenetic analysis suggests the horizontal transfer of the epsilon-Proteobacterial DsbAs from a common ancestor to gamma-Proteobacteria, which then gave rise to the DsbL lineage. Phenotype and enzymatic assays suggest that the two C. jejuni DsbAs play different roles in bacterial cells and have divergent substrate spectra. CjDsbA1 is essential for the motility and autoagglutination phenotypes, while CjDsbA2 has no impact on those processes. CjDsbA1 plays a critical role in the oxidative folding that ensures the activity of alkaline phosphatase CjPhoX, whereas CjDsbA2 is crucial for the activity of arylsulfotransferase CjAstA, encoded within the dsbA2-dsbB-astA operon. Conclusions: Our results show that CjDsbA1 is the primary thiol-oxidoreductase affecting life processes associated with bacterial spread and host colonization, as well as ensuring the oxidative folding of particular protein substrates. In contrast, CjDsbA2 activity does not affect the same processes and so far its oxidative folding activity has been demonstrated for one substrate, arylsulfotransferase CjAstA. The results suggest the cooperation between CjDsbA2 and CjDsbB. In the case of the CjDsbA1, this cooperation is not exclusive and there is probably another protein to be identified in C. jejuni cells that acts to re-oxidize CjDsbA1. Altogether the data presented here constitute the considerable insight to the Epsilonproteobacterial Dsb systems, which have been poorly understood so far.

Functional deficiency of MHC class i enhances LTP and abolishes LTD in the nucleus accumbens of mice - Edamura, Mitsuhiro; Murakami, Gen; Meng, Hongrui; Itakura, Makoto; Shigemoto, Ryuichi; Fukuda, Atsuo; Nakahara, Daiichiro (PLoS One)
Major histocompatibility complex class I (MHCI) molecules were recently identified as novel regulators of synaptic plasticity. These molecules are expressed in various brain areas, especially in regions undergoing activity-dependent synaptic plasticity, but their role in the nucleus accumbens (NAc) is unknown. In this study, we investigated the effects of genetic disruption of MHCI function, through deletion of β2-microblobulin, which causes lack of cell surface expression of MHCI. First, we confirmed that MHCI molecules are expressed in the NAc core in wild-type mice. Second, we performed electrophysiological recordings with NAc core slices from wild-type and β2-microglobulin knock-out mice lacking cell surface expression of MHCI. We found that low frequency stimulation induced long-term depression in wild-type but not knock-out mice, whereas high frequency stimulation induced long-term potentiation in both genotypes, with a larger magnitude in knock-out mice. Furthermore, we demonstrated that knock-out mice showed more persistent behavioral sensitization to cocaine, which is a NAc-related behavior. Using this model, we analyzed the density of total AMPA receptors and their subunits GluR1 and GluR2 in the NAc core, by SDS-digested freeze-fracture replica labeling. After repeated cocaine exposure, the density of GluR1 was increased, but there was no change in total AMPA receptors and GluR2 levels in wildtype mice. In contrast, following repeated cocaine exposure, increased densities of total AMPA receptors, GluR1 and GluR2 were observed in knock-out mice. These results indicate that functional deficiency of MHCI enhances synaptic potentiation, induced by electrical and pharmacological stimulation.

SAC phosphoinositide phosphatases at the tonoplast mediate vacuolar function in Arabidopsis - Nováková, Petra; Hirsch, Sibylle; Feraru, Elena; Tejos, Ricardo; Van Wijk, Ringo; Viaene, Tom; Heilmann, Mareike; Lerche, Jennifer; De Rycke, Riet; Feraru, Mugurel; Grones, Peter; Van Montagu, Marc; et al. (PNAS)
Phosphatidylinositol (PtdIns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, PtdIns3P and PtdIns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vacuolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with PtdIns3P, the presumable product of their activity. In SAC gain- and loss-of-function mutants, the levels of PtdIns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with PtdIns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Mathematical model of alternative mechanism of telomere length maintenance - Kollár, Richard; Bod'ová, Katarína; Nosek, Jozef; Tomáška, Ľubomír (Physical Review E Statistical Nonlinear and Soft Matter Physics)
Biopolymer length regulation is a complex process that involves a large number of biological, chemical, and physical subprocesses acting simultaneously across multiple spatial and temporal scales. An illustrative example important for genomic stability is the length regulation of telomeres - nucleoprotein structures at the ends of linear chromosomes consisting of tandemly repeated DNA sequences and a specialized set of proteins. Maintenance of telomeres is often facilitated by the enzyme telomerase but, particularly in telomerase-free systems, the maintenance of chromosomal termini depends on alternative lengthening of telomeres (ALT) mechanisms mediated by recombination. Various linear and circular DNA structures were identified to participate in ALT, however, dynamics of the whole process is still poorly understood. We propose a chemical kinetics model of ALT with kinetic rates systematically derived from the biophysics of DNA diffusion and looping. The reaction system is reduced to a coagulation-fragmentation system by quasi-steady-state approximation. The detailed treatment of kinetic rates yields explicit formulas for expected size distributions of telomeres that demonstrate the key role played by the J factor, a quantitative measure of bending of polymers. The results are in agreement with experimental data and point out interesting phenomena: an appearance of very long telomeric circles if the total telomere density exceeds a critical value (excess mass) and a nonlinear response of the telomere size distributions to the amount of telomeric DNA in the system. The results can be of general importance for understanding dynamics of telomeres in telomerase-independent systems as this mode of telomere maintenance is similar to the situation in tumor cells lacking telomerase activity. Furthermore, due to its universality, the model may also serve as a prototype of an interaction between linear and circular DNA structures in various settings.

Insights into the localization and function of the membrane trafficking regulator GNOM ARF-GEF at the Golgi apparatus in Arabidopsis - Naramoto, Satoshi; Otegui, Marisa; Kutsuna, Natsumaro; De Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jirí (Plant Cell)
GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana. State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans-Golgi network (TGN)/early endosomes (EEs). Malformed TGN/EE in gnom mutants suggests a role for GNOM in maintaining TGN/EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.

Par3-mInsc and Gα i3 cooperate to promote oriented epidermal cell divisions through LGN - Williams, Scott; Ratliff, Lyndsay; Postiglione, Maria P; Knoblich, Juergen; Fuchs, Elaine (Nature Cell Biology)
Asymmetric cell divisions allow stem cells to balance proliferation and differentiation. During embryogenesis, murine epidermis expands rapidly from a single layer of unspecified basal layer progenitors to a stratified, differentiated epithelium. Morphogenesis involves perpendicular (asymmetric) divisions and the spindle orientation protein LGN, but little is known about how the apical localization of LGN is regulated. Here, we combine conventional genetics and lentiviral-mediated in vivo RNAi to explore the functions of the LGN-interacting proteins Par3, mInsc and Gα i3. Whereas loss of each gene alone leads to randomized division angles, combined loss of Gnai3 and mInsc causes a phenotype of mostly planar divisions, akin to loss of LGN. These findings lend experimental support for the hitherto untested model that Par3-mInsc and Gα i3 act cooperatively to polarize LGN and promote perpendicular divisions. Finally, we uncover a developmental switch between delamination-driven early stratification and spindle-orientation-dependent differentiation that occurs around E15, revealing a two-step mechanism underlying epidermal maturation.

Ultrafast action potentials mediate kilohertz signaling at a central synapse - Ritzau Jost, Andreas; Delvendahl, Igor; Rings, Annika; Byczkowicz, Niklas; Harada, Harumi; Shigemoto, Ryuichi; Hirrlinger, Johannes; Eilers, Jens; Hallermann, Stefan (Neuron)
Fast synaptic transmission is important for rapid information processing. To explore the maximal rate of neuronal signaling and to analyze the presynaptic mechanisms, we focused on the input layer of the cerebellar cortex, where exceptionally high action potential (AP) frequencies have been reported invivo. With paired recordings between presynaptic cerebellar mossy fiber boutons and postsynaptic granule cells, we demonstrate reliable neurotransmission upto ~1 kHz. Presynaptic APs are ultrafast, with ~100μs half-duration. Both Kv1 and Kv3 potassium channels mediate the fast repolarization, rapidly inactivating sodium channels ensure metabolic efficiency, and little AP broadening occurs during bursts of up to 1.5 kHz. Presynaptic Cav2.1 (P/Q-type) calcium channels open efficiently during ultrafast APs. Furthermore, a subset of synaptic vesicles is tightly coupled to Ca2+ channels, and vesicles are rapidly recruited to the release site. These data reveal mechanisms of presynaptic AP generation and transmitter release underlying neuronal kHz signaling.

Large-scale point-cloud visualization through localized textured surface reconstruction - Arikan, Murat; Preiner, Reinhold; Scheiblauer, Claus; Jeschke, Stefan; Wimmer, Michael (IEEE Transactions on Visualization and Computer Graphics)
In this paper, we introduce a novel scene representation for the visualization of large-scale point clouds accompanied by a set of high-resolution photographs. Many real-world applications deal with very densely sampled point-cloud data, which are augmented with photographs that often reveal lighting variations and inaccuracies in registration. Consequently, the high-quality representation of the captured data, i.e., both point clouds and photographs together, is a challenging and time-consuming task. We propose a two-phase approach, in which the first (preprocessing) phase generates multiple overlapping surface patches and handles the problem of seamless texture generation locally for each patch. The second phase stitches these patches at render-time to produce a high-quality visualization of the data. As a result of the proposed localization of the global texturing problem, our algorithm is more than an order of magnitude faster than equivalent mesh-based texturing techniques. Furthermore, since our preprocessing phase requires only a minor fraction of the whole data set at once, we provide maximum flexibility when dealing with growing data sets.

Selection from parasites favours immunogenetic diversity but not divergence among locally adapted host populations - Tobler, Michael; Plath, Martin; Riesch, Rüdiger; Schlupp, Ingo; Grasse, Anna V; Munimanda, Gopi; Setzer, C; Penn, Dustin; Moodley, Yoshan (Journal of Evolutionary Biology)
The unprecedented polymorphism in the major histocompatibility complex (MHC) genes is thought to be maintained by balancing selection from parasites. However, do parasites also drive divergence at MHC loci between host populations, or do the effects of balancing selection maintain similarities among populations? We examined MHC variation in populations of the livebearing fish Poecilia mexicana and characterized their parasite communities. Poecilia mexicana populations in the Cueva del Azufre system are locally adapted to darkness and the presence of toxic hydrogen sulphide, representing highly divergent ecotypes or incipient species. Parasite communities differed significantly across populations, and populations with higher parasite loads had higher levels of diversity at class II MHC genes. However, despite different parasite communities, marked divergence in adaptive traits and in neutral genetic markers, we found MHC alleles to be remarkably similar among host populations. Our findings indicate that balancing selection from parasites maintains immunogenetic diversity of hosts, but this process does not promote MHC divergence in this system. On the contrary, we suggest that balancing selection on immunogenetic loci may outweigh divergent selection causing divergence, thereby hindering host divergence and speciation. Our findings support the hypothesis that balancing selection maintains MHC similarities among lineages during and after speciation (trans-species evolution).

Growth rates made easy - Hall, Barry; Acar, Hande; Nandipati, Anna; Barlow, Miriam (Molecular Biology and Evolution)
In the 1960s-1980s, determination of bacterial growth rates was an important tool in microbial genetics, biochemistry, molecular biology, and microbial physiology. The exciting technical developments of the 1990s and the 2000s eclipsed that tool; as a result, many investigators today lack experience with growth rate measurements. Recently, investigators in a number of areas have started to use measurements of bacterial growth rates for a variety of purposes. Those measurements have been greatly facilitated by the availability of microwell plate readers that permit the simultaneous measurements on up to 384 different cultures. Only the exponential (logarithmic) portions of the resulting growth curves are useful for determining growth rates, and manual determination of that portion and calculation of growth rates can be tedious for high-throughput purposes. Here, we introduce the program GrowthRates that uses plate reader output files to automatically determine the exponential portion of the curve and to automatically calculate the growth rate, the maximum culture density, and the duration of the growth lag phase. GrowthRates is freely available for Macintosh, Windows, and Linux.We discuss the effects of culture volume, the classical bacterial growth curve, and the differences between determinations in rich media and minimal (mineral salts) media. This protocol covers calibration of the plate reader, growth of culture inocula for both rich and minimal media, and experimental setup. As a guide to reliability, we report typical day-to-day variation in growth rates and variation within experiments with respect to position of wells within the plates.

WOX5-IAA17 feedback circuit-mediated cellular auxin response is crucial for the patterning of root stem cell niches in arabidopsis - Tian, Huiyu; Wabnik, Krzysztof T; Niu, Tiantian; Li, Hongjiang; Yu, Qianqian; Pollmann, Stephan; Vanneste, Steffen; Govaerts, Willy; Rolčík, Jakub; Geisler, Markus; Friml, Jirí; Ding, Zhaojun (Molecular Plant)
In plants, the patterning of stem cell-enriched meristems requires a graded auxin response maximum that emerges from the concerted action of polar auxin transport, auxin biosynthesis, auxin metabolism, and cellular auxin response machinery. However, mechanisms underlying this auxin response maximum-mediated root stem cell maintenance are not fully understood. Here, we present unexpected evidence that WUSCHEL-RELATED HOMEOBOX 5 (WOX5) transcription factor modulates expression of auxin biosynthetic genes in the quiescent center (QC) of the root and thus provides a robust mechanism for the maintenance of auxin response maximum in the root tip. This WOX5 action is balanced through the activity of indole-3-acetic acid 17 (IAA17) auxin response repressor. Our combined genetic, cell biology, and computational modeling studies revealed a previously uncharacterized feedback loop linking WOX5-mediated auxin production to IAA17-dependent repression of auxin responses. This WOX5-IAA17 feedback circuit further assures the maintenance of auxin response maximum in the root tip and thereby contributes to the maintenance of distal stem cell (DSC) populations. Our experimental studies and in silico computer simulations both demonstrate that the WOX5-IAA17 feedback circuit is essential for the maintenance of auxin gradient in the root tip and the auxin-mediated root DSC differentiation.

Strichartz inequality for orthonormal functions - Frank, Rupert; Lewin, Mathieu; Lieb, Élliott; Seiringer, Robert (Journal of the European Mathematical Society)
We prove a Strichartz inequality for a system of orthonormal functions, with an optimal behavior of the constant in the limit of a large number of functions. The estimate generalizes the usual Strichartz inequality, in the same fashion as the Lieb-Thirring inequality generalizes the Sobolev inequality. As an application, we consider the Schrödinger equation with a time-dependent potential and we show the existence of the wave operator in Schatten spaces.

Lateral junction dynamics lead the way out - Behrndt, Martin; Heisenberg, Carl-Philipp J (Nature Cell Biology)
Epithelial cell layers need to be tightly regulated to maintain their integrity and correct function. Cell integration into epithelial sheets is now shown to depend on the N-WASP-regulated stabilization of cortical F-actin, which generates distinct patterns of apical-lateral contractility at E-cadherin-based cell-cell junctions.

The fitness costs of adaptation via phenotypic plasticity and maternal effects - Ezard, Thomas; Prizak, Roshan; Hoyle, Rebecca (Functional Ecology)
Summary: Phenotypes are often environmentally dependent, which requires organisms to track environmental change. The challenge for organisms is to construct phenotypes using the most accurate environmental cue. Here, we use a quantitative genetic model of adaptation by additive genetic variance, within- and transgenerational plasticity via linear reaction norms and indirect genetic effects respectively. We show how the relative influence on the eventual phenotype of these components depends on the predictability of environmental change (fast or slow, sinusoidal or stochastic) and the developmental lag τ between when the environment is perceived and when selection acts. We then decompose expected mean fitness into three components (variance load, adaptation and fluctuation load) to study the fitness costs of within- and transgenerational plasticity. A strongly negative maternal effect coefficient m minimizes the variance load, but a strongly positive m minimises the fluctuation load. The adaptation term is maximized closer to zero, with positive or negative m preferred under different environmental scenarios. Phenotypic plasticity is higher when τ is shorter and when the environment changes frequently between seasonal extremes. Expected mean population fitness is highest away from highest observed levels of phenotypic plasticity. Within- and transgenerational plasticity act in concert to deliver well-adapted phenotypes, which emphasizes the need to study both simultaneously when investigating phenotypic evolution.

Langerhans cell maturation is accompanied by induction of N-cadherin and the transcriptional regulators of epithelial-mesenchymal transition ZEB1/2 - Konradi, Sabine; Yasmin, Nighat; Haslwanter, Denise; Weber, Michele; Gesslbauer, Bernd; Sixt, Michael K; Strobl, Herbert (European Journal of Immunology)
angerhans cells (LCs) are a unique subset of dendritic cells (DCs) that express epithelial adhesion molecules, allowing them to form contacts with epithelial cells and reside in epidermal/epithelial tissues. The dynamic regulation of epithelial adhesion plays a decisive role in the life cycle of LCs. It controls whether LCs remain immature and sessile within the epidermis or mature and egress to initiate immune responses. So far, the molecular machinery regulating epithelial adhesion molecules during LC maturation remains elusive. Here, we generated pure populations of immature human LCs in vitro to systematically probe for gene-expression changes during LC maturation. LCs down-regulate a set of epithelial genes including E-cadherin, while they upregulate the mesenchymal marker N-cadherin known to facilitate cell migration. In addition, N-cadherin is constitutively expressed by monocyte-derived DCs known to exhibit characteristics of both inflammatory-type and interstitial/dermal DCs. Moreover, the transcription factors ZEB1 and ZEB2 (ZEB is zinc-finger E-box-binding homeobox) are upregulated in migratory LCs. ZEB1 and ZEB2 have been shown to induce epithelial-to-mesenchymal transition (EMT) and invasive behavior in cancer cells undergoing metastasis. Our results provide the first hint that the molecular EMT machinery might facilitate LC mobilization. Moreover, our study suggests that N-cadherin plays a role during DC migration.

Optimality of non-adaptive strategies: The case of parallel games - Demay, Grégory; Gazi, Peter; Maurer, Ueli; Tackmann, Björn (IEEE International Symposium on Information Theory)
Most cryptographic security proofs require showing that two systems are indistinguishable. A central tool in such proofs is that of a game, where winning the game means provoking a certain condition, and it is shown that the two systems considered cannot be distinguished unless this condition is provoked. Upper bounding the probability of winning such a game, i.e., provoking this condition, for an arbitrary strategy is usually hard, except in the special case where the best strategy for winning such a game is known to be non-adaptive. A sufficient criterion for ensuring the optimality of non-adaptive strategies is that of conditional equivalence to a system, a notion introduced in [1]. In this paper, we show that this criterion is not necessary to ensure the optimality of non-adaptive strategies by giving two results of independent interest: 1) the optimality of non-adaptive strategies is not preserved under parallel composition; 2) in contrast, conditional equivalence is preserved under parallel composition.

The rate of adaptation in large sexual populations with linear chromosomes - Weissman, Daniel; Hallatschek, Oskar (Genetics)
In large populations, multiple beneficial mutations may be simultaneously spreading. In asexual populations, these mutations must either arise on the same background or compete against each other. In sexual populations, recombination can bring together beneficial alleles from different backgrounds, but tightly linked alleles may still greatly interfere with each other. We show for well-mixed populations that when this interference is strong, the genome can be seen as consisting of many effectively asexual stretches linked together. The rate at which beneficial alleles fix is thus roughly proportional to the rate of recombination and depends only logarithmically on the mutation supply and the strength of selection. Our scaling arguments also allow us to predict, with reasonable accuracy, the fitness distribution of fixed mutations when the mutational effect sizes are broad. We focus on the regime in which crossovers occur more frequently than beneficial mutations, as is likely to be the case for many natural populations.

Tverberg's Theorem and Graph Coloring - Engström, Alexander; Noren, Patrik (Discrete & Computational Geometry)
The topological Tverberg theorem has been generalized in several directions by setting extra restrictions on the Tverberg partitions. Restricted Tverberg partitions, defined by the idea that certain points cannot be in the same part, are encoded with graphs. When two points are adjacent in the graph, they are not in the same part. If the restrictions are too harsh, then the topological Tverberg theorem fails. The colored Tverberg theorem corresponds to graphs constructed as disjoint unions of small complete graphs. Hell studied the case of paths and cycles. In graph theory these partitions are usually viewed as graph colorings. As explored by Aharoni, Haxell, Meshulam and others there are fundamental connections between several notions of graph colorings and topological combinatorics. For ordinary graph colorings it is enough to require that the number of colors q satisfy q>Δ, where Δ is the maximal degree of the graph. It was proven by the first author using equivariant topology that if q>Δ 2 then the topological Tverberg theorem still works. It is conjectured that q>KΔ is also enough for some constant K, and in this paper we prove a fixed-parameter version of that conjecture. The required topological connectivity results are proven with shellability, which also strengthens some previous partial results where the topological connectivity was proven with the nerve lemma.

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders - Novarino, Gaia; Fenstermaker, Ali; Zaki, Maha; Hofree, Matan; Silhavy, Jennifer; Heiberg, Andrew; Abdellateef, Mostafa; Rosti, Başak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.

Cell surface ABP1-TMK auxin sensing complex activates ROP GTPase signaling - Xu, Tongda; Dai, Ning; Chen, Jisheng; Nagawa, Shingo; Cao, Min; Li, Hongjiang; Zhou, Zimin; Chen, Xu; De Rycke, Riet; Rakusová, Hana; Wang, Wen; Jones, Alan; et al. (Science)
Auxin-binding protein 1 (ABP1) was discovered nearly 40 years ago and was shown to be essential for plant development and morphogenesis, but its mode of action remains unclear. Here, we report that the plasma membrane-localized transmembrane kinase (TMK) receptor-like kinases interact with ABP1 and transduce auxin signal to activate plasma membrane-associated ROPs [Rho-like guanosine triphosphatases (GTPase) from plants], leading to changes in the cytoskeleton and the shape of leaf pavement cells in Arabidopsis. The interaction between ABP1 and TMK at the cell surface is induced by auxin and requires ABP1 sensing of auxin. These findings show that TMK proteins and ABP1 form a cell surface auxin perception complex that activates ROP signaling pathways, regulating nontranscriptional cytoplasmic responses and associated fundamental processes.

Distinct cerebellar engrams in short-term and long-term motor learning - Wang, Wen; Nakadate, Kazuhiko; Masugi Tokita, Miwako; Shutoh, Fumihiro; Aziz, Wajeeha; Tarusawa, Etsuko; Lörincz, Andrea; Molnár, Elek; Kesaf, Sebnem; Li, Yunqing; Fukazawa, Yugo; Nagao, Soichi; et al. (PNAS)
Cerebellar motor learning is suggested to be caused by long-term plasticity of excitatory parallel fiber-Purkinje cell (PF-PC) synapses associated with changes in the number of synaptic AMPA-type glutamate receptors (AMPARs). However, whether the AMPARs decrease or increase in individual PF-PC synapses occurs in physiological motor learning and accounts for memory that lasts over days remains elusive. We combined quantitative SDS-digested freeze-fracture replica labeling for AMPAR and physical dissector electron microscopy with a simple model of cerebellar motor learning, adaptation of horizontal optokinetic response (HOKR) in mouse. After 1-h training of HOKR, short-term adaptation (STA) was accompanied with transient decrease in AMPARs by 28% in target PF-PC synapses. STA was well correlated with AMPAR decrease in individual animals and both STA and AMPAR decrease recovered to basal levels within 24 h. Surprisingly, long-termadaptation (LTA) after five consecutive daily trainings of 1-h HOKR did not alter the number of AMPARs in PF-PC synapses but caused gradual and persistent synapse elimination by 45%, with corresponding PC spine loss by the fifth training day. Furthermore, recovery of LTA after 2 wk was well correlated with increase of PF-PC synapses to the control level. Our findings indicate that the AMPARs decrease in PF-PC synapses and the elimination of these synapses are in vivo engrams in short- and long-term motor learning, respectively, showing a unique type of synaptic plasticity that may contribute to memory consolidation.

Rho-GTPase-regulated vesicle trafficking in plant cell polarity - Chen, Xu; Friml, Jirí (Biochemical Society Transactions)
ROPs (Rho of plants) belong to a large family of plant-specific Rho-like small GTPases that function as essential molecular switches to control diverse cellular processes including cytoskeleton organization, cell polarization, cytokinesis, cell differentiation and vesicle trafficking. Although the machineries of vesicle trafficking and cell polarity in plants have been individually well addressed, how ROPs co-ordinate those processes is still largely unclear. Recent progress has been made towards an understanding of the coordination of ROP signalling and trafficking of PIN (PINFORMED) transporters for the plant hormone auxin in both root and leaf pavement cells. PIN transporters constantly shuttle between the endosomal compartments and the polar plasma membrane domains, therefore the modulation of PIN-dependent auxin transport between cells is a main developmental output of ROP-regulated vesicle trafficking. The present review focuses on these cellular mechanisms, especially the integration of ROP-based vesicle trafficking and plant cell polarity.

Distinct kinetics of synaptic structural plasticity, memory formation, and memory decay in massed and spaced learning - Aziz, Wajeeha; Wang, Wen; Kesaf, Sebnem; Mohamed, Alsayed; Fukazawa, Yugo; Shigemoto, Ryuichi (PNAS)
Long-lasting memories are formed when the stimulus is temporally distributed (spacing effect). However, the synaptic mechanisms underlying this robust phenomenon and the precise time course of the synaptic modifications that occur during learning remain unclear. Here we examined the adaptation of horizontal optokinetic response in mice that underwent 1 h of massed and spaced training at varying intervals. Despite similar acquisition by all training protocols, 1 h of spacing produced the highest memory retention at 24 h, which lasted for 1 mo. The distinct kinetics of memory are strongly correlated with the reduction of floccular parallel fiber-Purkinje cell synapses but not with AMPA receptor (AMPAR) number and synapse size. After the spaced training, we observed 25%, 23%, and 12% reduction in AMPAR density, synapse size, and synapse number, respectively. Four hours after the spaced training, half of the synapses and Purkinje cell spines had been eliminated, whereas AMPAR density and synapse size were recovered in remaining synapses. Surprisingly, massed training also produced long-term memory and halving of synapses; however, this occurred slowly over days, and the memory lasted for only 1 wk. This distinct kinetics of structural plasticity may serve as a basis for unique temporal profiles in the formation and decay of memory with or without intervals.

Existence of ground states for negative ions at the binding threshold - Bellazzini, Jacopo; Frank, Rupert; Lieb, Élliott; Seiringer, Robert (Reviews in Mathematical Physics)
As the nuclear charge Z is continuously decreased an N-electron atom undergoes a binding-unbinding transition. We investigate whether the electrons remain bound and whether the radius of the system stays finite as the critical value Zc is approached. Existence of a ground state at Zc is shown under the condition Zc < N-K, where K is the maximal number of electrons that can be removed at Zc without changing the energy.

Plant biology: Gatekeepers of the road to protein perdition - Sauer, Michael; Friml, Jirí (Current Biology)
Targeting membrane proteins for degradation requires the sequential action of ESCRT sub-complexes ESCRT-0 to ESCRT-III. Although this machinery is generally conserved among kingdoms, plants lack the essential ESCRT-0 components. A new report closes this gap by identifying a novel protein family that substitutes for ESCRT-0 function in plants.

A single-molecule approach to explore binding uptake and transport of cancer cell targeting nanotubes - Lamprecht, Constanze; Plochberger, Birgit; Ruprecht, Verena; Wieser, Stefan; Rankl, Christian; Heister, Elena; Unterauer, Barbara; Brameshuber, Mario; Danzberger, Jürgen; Lukanov, Petar; Flahaut, Emmanuel; Schütz, Gerhard; et al. (Nanotechnology)
In the past decade carbon nanotubes (CNTs) have been widely studied as a potential drug-delivery system, especially with functionality for cellular targeting. Yet, little is known about the actual process of docking to cell receptors and transport dynamics after internalization. Here we performed single-particle studies of folic acid (FA) mediated CNT binding to human carcinoma cells and their transport inside the cytosol. In particular, we employed molecular recognition force spectroscopy, an atomic force microscopy based method, to visualize and quantify docking of FA functionalized CNTs to FA binding receptors in terms of binding probability and binding force. We then traced individual fluorescently labeled, FA functionalized CNTs after specific uptake, and created a dynamic 'roadmap' that clearly showed trajectories of directed diffusion and areas of nanotube confinement in the cytosol. Our results demonstrate the potential of a single-molecule approach for investigation of drug-delivery vehicles and their targeting capacity.

Active elastic thin shell theory for cellular deformations - Berthoumieux, Hélène; Maître, Jean-Léon; Heisenberg, Carl-Philipp J; Paluch, Ewa; Julicher, Frank; Salbreux, Guillaume (New Journal of Physics)
We derive the equations for a thin, axisymmetric elastic shell subjected to an internal active stress giving rise to active tension and moments within the shell. We discuss the stability of a cylindrical elastic shell and its response to a localized change in internal active stress. This description is relevant to describe the cellular actomyosin cortex, a thin shell at the cell surface behaving elastically at a short timescale and subjected to active internal forces arising from myosin molecular motor activity. We show that the recent observations of cell deformation following detachment of adherent cells (Maître J-L et al 2012 Science 338 253-6) are well accounted for by this mechanical description. The actin cortex elastic and bending moduli can be obtained from a quantitative analysis of cell shapes observed in these experiments. Our approach thus provides a non-invasive, imaging-based method for the extraction of cellular physical parameters.

Bipolar plasma membrane distribution of phosphoinositides and their requirement for auxin-mediated cell polarity and patterning in Arabidopsis - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, MiriamPalacios; Li, Hongjiang; Heilmann, Mareike; Van Wijk, Ringo; Vermeer, Joop; Heilmann, Ingo; Munnik, Teun; Friml, Jirí (Plant Cell)
Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM. Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain-delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.

Dynamic infrared imaging analysis of apical hook development in Arabidopsis: The case of brassinosteroids - Smet, Dajo; Žádníková, Petra; Vandenbussche, Filip; Benková, Eva; Van Der Straeten, Dominique (New Phytologist)
Germination of Arabidopsis seeds in darkness induces apical hook development, based on a tightly regulated differential growth coordinated by a multiple hormone cross-talk. Here, we endeavoured to clarify the function of brassinosteroids (BRs) and cross-talk with ethylene in hook development. An automated infrared imaging system was developed to study the kinetics of hook development in etiolated Arabidopsis seedlings. To ascertain the photomorphogenic control of hook opening, the system was equipped with an automatic light dimmer. We demonstrate that ethylene and BRs are indispensable for hook formation and maintenance. Ethylene regulation of hook formation functions partly through BRs, with BR feedback inhibition of ethylene action. Conversely, BR-mediated extension of hook maintenance functions partly through ethylene. Furthermore, we revealed that a short light pulse is sufficient to induce rapid hook opening. Our dynamic infrared imaging system allows high-resolution, kinetic imaging of up to 112 seedlings in a single experimental run. At this high throughput, it is ideally suited to rapidly gain insight in pathway networks. We demonstrate that BRs and ethylene cooperatively regulate apical hook development in a phase-dependent manner. Furthermore, we show that light is a predominant regulator of hook opening, inhibiting ethylene- and BR-mediated postponement of hook opening.

Absolutely continuous spectrum for random Schrödinger operators on the Fibonacci and similar Tree-strips - Sadel, Christian (Mathematical Physics, Analysis and Geometry)
We consider cross products of finite graphs with a class of trees that have arbitrarily but finitely long line segments, such as the Fibonacci tree. Such cross products are called tree-strips. We prove that for small disorder random Schrödinger operators on such tree-strips have purely absolutely continuous spectrum in a certain set.

Auxin transport and activity regulate stomatal patterning and development - Le, Jie; Liu, Xuguang; Yang, Kezhen; Chen, Xiaolan; Zhu, Lingling; Wang, Hongzhe; Wang, Ming; Vanneste, Steffen; Morita, Miyo; Tasaka, Masao; Ding, Zhaojun; Friml, Jirí; et al. (Nature Communications)
Stomata are two-celled valves that control epidermal pores whose spacing optimizes shoot-atmosphere gas exchange. They develop from protodermal cells after unequal divisions followed by an equal division and differentiation. The concentration of the hormone auxin, a master plant developmental regulator, is tightly controlled in time and space, but its role, if any, in stomatal formation is obscure. Here dynamic changes of auxin activity during stomatal development are monitored using auxin input (DII-VENUS) and output (DR5:VENUS) markers by time-lapse imaging. A decrease in auxin levels in the smaller daughter cell after unequal division presages the acquisition of a guard mother cell fate whose equal division produces the two guard cells. Thus, stomatal patterning requires auxin pathway control of stem cell compartment size, as well as auxin depletion that triggers a developmental switch from unequal to equal division.

Evolutionary dynamics of infectious diseases in finite populations - Humplik, Jan; Hill, Alison; Nowak, Martin (Journal of Theoretical Biology)
In infectious disease epidemiology the basic reproductive ratio, R0, is defined as the average number of new infections caused by a single infected individual in a fully susceptible population. Many models describing competition for hosts between non-interacting pathogen strains in an infinite population lead to the conclusion that selection favors invasion of new strains if and only if they have higher R0 values than the resident. Here we demonstrate that this picture fails in finite populations. Using a simple stochastic SIS model, we show that in general there is no analogous optimization principle. We find that successive invasions may in some cases lead to strains that infect a smaller fraction of the host population, and that mutually invasible pathogen strains exist. In the limit of weak selection we demonstrate that an optimization principle does exist, although it differs from R0 maximization. For strains with very large R0, we derive an expression for this local fitness function and use it to establish a lower bound for the error caused by neglecting stochastic effects. Furthermore, we apply this weak selection limit to investigate the selection dynamics in the presence of a trade-off between the virulence and the transmission rate of a pathogen.

An algorithm for cartographic generalization that preserves global topology - Alexeev, V V; Bogaevskaya, V G; Preobrazhenskaya, M M; Ukhalov, A Y; Edelsbrunner, Herbert; Yakimova, Olga (Journal of Mathematical Sciences)
We propose an algorithm for the generalization of cartographic objects that can be used to represent maps on different scales.

Formation of stripes and slabs near the ferromagnetic transition - Giuliani, Alessandro; Lieb, Élliott; Seiringer, Robert (Communications in Mathematical Physics)
We consider Ising models in d = 2 and d = 3 dimensions with nearest neighbor ferromagnetic and long-range antiferromagnetic interactions, the latter decaying as (distance)-p, p > 2d, at large distances. If the strength J of the ferromagnetic interaction is larger than a critical value J c, then the ground state is homogeneous. It has been conjectured that when J is smaller than but close to J c, the ground state is periodic and striped, with stripes of constant width h = h(J), and h → ∞ as J → Jc -. (In d = 3 stripes mean slabs, not columns.) Here we rigorously prove that, if we normalize the energy in such a way that the energy of the homogeneous state is zero, then the ratio e 0(J)/e S(J) tends to 1 as J → Jc -, with e S(J) being the energy per site of the optimal periodic striped/slabbed state and e 0(J) the actual ground state energy per site of the system. Our proof comes with explicit bounds on the difference e 0(J)-e S(J) at small but positive J c-J, and also shows that in this parameter range the ground state is striped/slabbed in a certain sense: namely, if one looks at a randomly chosen window, of suitable size ℓ (very large compared to the optimal stripe size h(J)), one finds a striped/slabbed state with high probability.

An arms race between producers and scroungers can drive the evolution of social cognition - Arbilly, Michal; Weissman, Daniel; Feldman, Marcus; Grodzinski, Uri (Behavioral Ecology)
The social intelligence hypothesis states that the need to cope with complexities of social life has driven the evolution of advanced cognitive abilities. It is usually invoked in the context of challenges arising from complex intragroup structures, hierarchies, and alliances. However, a fundamental aspect of group living remains largely unexplored as a driving force in cognitive evolution: the competition between individuals searching for resources (producers) and conspecifics that parasitize their findings (scroungers). In populations of social foragers, abilities that enable scroungers to steal by outsmarting producers, and those allowing producers to prevent theft by outsmarting scroungers, are likely to be beneficial and may fuel a cognitive arms race. Using analytical theory and agent-based simulations, we present a general model for such a race that is driven by the producer-scrounger game and show that the race's plausibility is dramatically affected by the nature of the evolving abilities. If scrounging and scrounging avoidance rely on separate, strategy-specific cognitive abilities, arms races are short-lived and have a limited effect on cognition. However, general cognitive abilities that facilitate both scrounging and scrounging avoidance undergo stable, long-lasting arms races. Thus, ubiquitous foraging interactions may lead to the evolution of general cognitive abilities in social animals, without the requirement of complex intragroup structures.

Cytokinin controls polarity of PIN1-dependent Auxin transport during lateral root organogenesis - Marhavy, Peter; Duclercq, Jérôme; Weller, Benjamin; Feraru, Elena; Bielach, Agnieszka; Offringa, Remko; Friml, Jirí; Schwechheimer, Claus; Murphy, Angus; Benková, Eva (Current Biology)
The plant hormones auxin and cytokinin mutually coordinate their activities to control various aspects of development [1-9], and their crosstalk occurs at multiple levels [10, 11]. Cytokinin-mediated modulation of auxin transport provides an efficient means to regulate auxin distribution in plant organs. Here, we demonstrate that cytokinin does not merely control the overall auxin flow capacity, but might also act as a polarizing cue and control the auxin stream directionality during plant organogenesis. Cytokinin enhances the PIN-FORMED1 (PIN1) auxin transporter depletion at specific polar domains, thus rearranging the cellular PIN polarities and directly regulating the auxin flow direction. This selective cytokinin sensitivity correlates with the PIN protein phosphorylation degree. PIN1 phosphomimicking mutations, as well as enhanced phosphorylation in plants with modulated activities of PIN-specific kinases and phosphatases, desensitize PIN1 to cytokinin. Our results reveal conceptually novel, cytokinin-driven polarization mechanism that operates in developmental processes involving rapid auxin stream redirection, such as lateral root organogenesis, in which a gradual PIN polarity switch defines the growth axis of the newly formed organ.

Cryptic genetic variation can make "irreducible complexity" a common mode of adaptation in sexual populations - Trotter, Meredith; Weissman, Daniel; Peterson, Grant; Peck, Kayla; Masel, Joanna (Evolution)
The existence of complex (multiple-step) genetic adaptations that are "irreducible" (i.e., all partial combinations are less fit than the original genotype) is one of the longest standing problems in evolutionary biology. In standard genetics parlance, these adaptations require the crossing of a wide adaptive valley of deleterious intermediate stages. Here, we demonstrate, using a simple model, that evolution can cross wide valleys to produce "irreducibly complex" adaptations by making use of previously cryptic mutations. When revealed by an evolutionary capacitor, previously cryptic mutants have higher initial frequencies than do new mutations, bringing them closer to a valley-crossing saddle in allele frequency space. Moreover, simple combinatorics implies an enormous number of candidate combinations exist within available cryptic genetic variation. We model the dynamics of crossing of a wide adaptive valley after a capacitance event using both numerical simulations and analytical approximations. Although individual valley crossing events become less likely as valleys widen, by taking the combinatorics of genotype space into account, we see that revealing cryptic variation can cause the frequent evolution of complex adaptations.

Fast and memory-efficient topological denoising of 2D and 3D scalar fields - Günther, David; Jacobson, Alec; Reininghaus, Jan; Seidel, Hans; Sorkine Hornung, Olga; Weinkauf, Tino (IEEE Transactions on Visualization and Computer Graphics)
(Figure Presented) Data acquisition, numerical inaccuracies, and sampling often introduce noise in measurements and simulations. Removing this noise is often necessary for efficient analysis and visualization of this data, yet many denoising techniques change the minima and maxima of a scalar field. For example, the extrema can appear or disappear, spatially move, and change their value. This can lead to wrong interpretations of the data, e.g., when the maximum temperature over an area is falsely reported being a few degrees cooler because the denoising method is unaware of these features. Recently, a topological denoising technique based on a global energy optimization was proposed, which allows the topology-controlled denoising of 2D scalar fields. While this method preserves the minima and maxima, it is constrained by the size of the data. We extend this work to large 2D data and medium-sized 3D data by introducing a novel domain decomposition approach. It allows processing small patches of the domain independently while still avoiding the introduction of new critical points. Furthermore, we propose an iterative refinement of the solution, which decreases the optimization energy compared to the previous approach and therefore gives smoother results that are closer to the input. We illustrate our technique on synthetic and real-world 2D and 3D data sets that highlight potential applications.

Cadherin-based adhesions in the apical endfoot are required for active Notch signaling to control neurogenesis in vertebrates - Hatakeyama, Jun; Wakamatsu, Yoshio; Nagafuchi, Akira; Kageyama, Ryoichiro; Shigemoto, Ryuichi; Shimamura, Kenji (Development)
The development of the vertebrate brain requires an exquisite balance between proliferation and differentiation of neural progenitors. Notch signaling plays a pivotal role in regulating this balance, yet the interaction between signaling and receiving cells remains poorly understood. We have found that numerous nascent neurons and/or intermediate neurogenic progenitors expressing the ligand of Notch retain apical endfeet transiently at the ventricular lumen that form adherens junctions (AJs) with the endfeet of progenitors. Forced detachment of the apical endfeet of those differentiating cells by disrupting AJs resulted in precocious neurogenesis that was preceded by the downregulation of Notch signaling. Both Notch1 and its ligand Dll1 are distributed around AJs in the apical endfeet, and these proteins physically interact with ZO-1, a constituent of the AJ. Furthermore, live imaging of a fluorescently tagged Notch1 demonstrated its trafficking from the apical endfoot to the nucleus upon cleavage. Our results identified the apical endfoot as the central site of active Notch signaling to securely prohibit inappropriate differentiation of neural progenitors.

Emergence of task-dependent representations in working memory circuits - Savin, Cristina; Triesch, Jochen (Frontiers in Computational Neuroscience)
A wealth of experimental evidence suggests that working memory circuits preferentially represent information that is behaviorally relevant. Still, we are missing a mechanistic account of how these representations come about. Here we provide a simple explanation for a range of experimental findings, in light of prefrontal circuits adapting to task constraints by reward-dependent learning. In particular, we model a neural network shaped by reward-modulated spike-timing dependent plasticity (r-STDP) and homeostatic plasticity (intrinsic excitability and synaptic scaling). We show that the experimentally-observed neural representations naturally emerge in an initially unstructured circuit as it learns to solve several working memory tasks. These results point to a critical, and previously unappreciated, role for reward-dependent learning in shaping prefrontal cortex activity.

Edge universality of beta ensembles - Bourgade, Paul; Erdös, László; Yau, Horngtzer (Communications in Mathematical Physics)
We prove the edge universality of the beta ensembles for any β ≥ 1, provided that the limiting spectrum is supported on a single interval, and the external potential is C4 and regular. We also prove that the edge universality holds for generalized Wigner matrices for all symmetry classes. Moreover, our results allow us to extend bulk universality for beta ensembles from analytic potentials to potentials in class C4.

Bimodal regulation of ICR1 levels generates self-organizing auxin distribution - Hazak, Ora; Obolski, Uri; Prat, Tomas; Friml, Jiří; Hadany, Lilach; Yalovsky, Shaul (PNAS)
Auxin polar transport, local maxima, and gradients have become an importantmodel system for studying self-organization. Auxin distribution is regulated by auxin-dependent positive feedback loops that are not well-understood at the molecular level. Previously, we showed the involvement of the RHO of Plants (ROP) effector INTERACTOR of CONSTITUTIVELY active ROP 1 (ICR1) in regulation of auxin transport and that ICR1 levels are posttranscriptionally repressed at the site of maximum auxin accumulation at the root tip. Here, we show that bimodal regulation of ICR1 levels by auxin is essential for regulating formation of auxin local maxima and gradients. ICR1 levels increase concomitant with increase in auxin response in lateral root primordia, cotyledon tips, and provascular tissues. However, in the embryo hypophysis and root meristem, when auxin exceeds critical levels, ICR1 is rapidly destabilized by an SCF(TIR1/AFB) [SKP, Cullin, F-box (transport inhibitor response 1/auxin signaling F-box protein)]-dependent auxin signaling mechanism. Furthermore, ectopic expression of ICR1 in the embryo hypophysis resulted in reduction of auxin accumulation and concomitant root growth arrest. ICR1 disappeared during root regeneration and lateral root initiation concomitantly with the formation of a local auxin maximum in response to external auxin treatments and transiently after gravitropic stimulation. Destabilization of ICR1 was impaired after inhibition of auxin transport and signaling, proteasome function, and protein synthesis. A mathematical model based on these findings shows that an in vivo-like auxin distribution, rootward auxin flux, and shootward reflux can be simulated without assuming preexisting tissue polarity. Our experimental results and mathematical modeling indicate that regulation of auxin distribution is tightly associated with auxin-dependent ICR1 levels.

Directional auxin transport mechanisms in early diverging land plants - Viaene, Tom; Landberg, Katarina; Thelander, Mattias; Medvecka, Eva; Pederson, Eric; Feraru, Elena; Cooper, Endymion; Karimi, Mansour; Delwiche, Charles; Ljung, Karin; Geisler, Markus; Sundberg, Eva; et al. (Current Biology)
The emergence and radiation of multicellular land plants was driven by crucial innovations to their body plans [1]. The directional transport of the phytohormone auxin represents a key, plant-specific mechanism for polarization and patterning in complex seed plants [2-5]. Here, we show that already in the early diverging land plant lineage, as exemplified by the moss Physcomitrella patens, auxin transport by PIN transporters is operational and diversified into ER-localized and plasma membrane-localized PIN proteins. Gain-of-function and loss-of-function analyses revealed that PIN-dependent intercellular auxin transport in Physcomitrella mediates crucial developmental transitions in tip-growing filaments and waves of polarization and differentiation in leaf-like structures. Plasma membrane PIN proteins localize in a polar manner to the tips of moss filaments, revealing an unexpected relation between polarization mechanisms in moss tip-growing cells and multicellular tissues of seed plants. Our results trace the origins of polarization and auxin-mediated patterning mechanisms and highlight the crucial role of polarized auxin transport during the evolution of multicellular land plants.

Fabry-Perot interferometer with quantum mirrors: Nonlinear light transport and rectification - Fratini, Filippo; Mascarenhas, Eduardo; Safari, Laleh; Poizat, Jean; Valente, Daniel; Auffèves, Alexia; Gerace, Dario; Santos, Marcelo (Physical Review Letters)
Optical transport represents a natural route towards fast communications, and it is currently used in large scale data transfer. The progressive miniaturization of devices for information processing calls for the microscopic tailoring of light transport and confinement at length scales appropriate for upcoming technologies. With this goal in mind, we present a theoretical analysis of a one-dimensional Fabry-Perot interferometer built with two highly saturable nonlinear mirrors: a pair of two-level systems. Our approach captures nonlinear and nonreciprocal effects of light transport that were not reported previously. Remarkably, we show that such an elementary device can operate as a microscopic integrated optical rectifier.

Individual and social immunisation in insects - El Masri, Leila; Cremer, Sylvia (Trends in Immunology)
Immune systems are able to protect the body against secondary infection with the same parasite. In insect colonies, this protection is not restricted to the level of the individual organism, but also occurs at the societal level. Here, we review recent evidence for and insights into the mechanisms underlying individual and social immunisation in insects. We disentangle general immune-protective effects from specific immune memory (priming), and examine immunisation in the context of the lifetime of an individual and that of a colony, and of transgenerational immunisation that benefits offspring. When appropriate, we discuss parallels with disease defence strategies in human societies. We propose that recurrent parasitic threats have shaped the evolution of both the individual immune systems and colony-level social immunity in insects.

Action potential modulation in CA1 pyramidal neuron axons facilitates OLM interneuron activation in recurrent inhibitory microcircuits of rat hippocampus - Kim, Sooyun (PLoS One)
Oriens-lacunosum moleculare (O-LM) interneurons in the CA1 region of the hippocampus play a key role in feedback inhibition and in the control of network activity. However, how these cells are efficiently activated in the network remains unclear. To address this question, I performed recordings from CA1 pyramidal neuron axons, the presynaptic fibers that provide feedback innervation of these interneurons. Two forms of axonal action potential (AP) modulation were identified. First, repetitive stimulation resulted in activity-dependent AP broadening. Broadening showed fast onset, with marked changes in AP shape following a single AP. Second, tonic depolarization in CA1 pyramidal neuron somata induced AP broadening in the axon, and depolarization-induced broadening summated with activity-dependent broadening. Outsideout patch recordings from CA1 pyramidal neuron axons revealed a high density of a-dendrotoxin (α-DTX)-sensitive, inactivating K+ channels, suggesting that K+ channel inactivation mechanistically contributes to AP broadening. To examine the functional consequences of axonal AP modulation for synaptic transmission, I performed paired recordings between synaptically connected CA1 pyramidal neurons and O-LM interneurons. CA1 pyramidal neuron-O-LM interneuron excitatory postsynaptic currents (EPSCs) showed facilitation during both repetitive stimulation and tonic depolarization of the presynaptic neuron. Both effects were mimicked and occluded by α-DTX, suggesting that they were mediated by K+ channel inactivation. Therefore, axonal AP modulation can greatly facilitate the activation of O-LM interneurons. In conclusion, modulation of AP shape in CA1 pyramidal neuron axons substantially enhances the efficacy of principal neuron-interneuron synapses, promoting the activation of O-LM interneurons in recurrent inhibitory microcircuits.

Learning by example in the hippocampus - O'Neill, Joseph; Csicsvari, Jozsef L (Neuron)
Learning can be facilitated by previous knowledge when it is organized into relational representations forming schemas. In this issue of Neuron, McKenzie et al. (2014) demonstrate that the hippocampus rapidly forms interrelated, hierarchical memory representations to support schema-based learning.

Scalable privacy-preserving data sharing methodology for genome-wide association studies - Yu, Fei; Fienberg, Stephen; Slaković, Alexandra; Uhler, Caroline (Journal of Biomedical Informatics)
The protection of privacy of individual-level information in genome-wide association study (GWAS) databases has been a major concern of researchers following the publication of “an attack” on GWAS data by Homer et al. (2008). Traditional statistical methods for confidentiality and privacy protection of statistical databases do not scale well to deal with GWAS data, especially in terms of guarantees regarding protection from linkage to external information. The more recent concept of differential privacy, introduced by the cryptographic community, is an approach that provides a rigorous definition of privacy with meaningful privacy guarantees in the presence of arbitrary external information, although the guarantees may come at a serious price in terms of data utility. Building on such notions, Uhler et al. (2013) proposed new methods to release aggregate GWAS data without compromising an individual’s privacy. We extend the methods developed in Uhler et al. (2013) for releasing differentially-private χ2χ2-statistics by allowing for arbitrary number of cases and controls, and for releasing differentially-private allelic test statistics. We also provide a new interpretation by assuming the controls’ data are known, which is a realistic assumption because some GWAS use publicly available data as controls. We assess the performance of the proposed methods through a risk-utility analysis on a real data set consisting of DNA samples collected by the Wellcome Trust Case Control Consortium and compare the methods with the differentially-private release mechanism proposed by Johnson and Shmatikov (2013).

Turning heads to remember places - Dupret, David; Csicsvari, Jozsef L (Nature Neuroscience)
By eliciting a natural exploratory behavior in rats, head scanning, a study reveals that hippocampal place cells form new, stable firing fields in those locations where the behavior has just occurred.

gIPFrm: Generalized iterative proportional fitting for relational models - Klimova, Anna; Rudas, Tamás
Maximum likelihood estimation under relational models, with or without the overall effect. For more information see the reference manual

Netrin-G/NGL complexes encode functional synaptic diversification - Matsukawa, Hiroshi; Akiyoshi Nishimura, Sachiko; Zhang, Qi; Luján, Rafael; Yamaguchi, Kazuhiko; Goto, Hiromichi; Yaguchi, Kunio; Hashikawa, Tsutomu; Sano, Chie; Shigemoto, Ryuichi; Nakashiba, Toshiaki; Itohara, Shigeyoshi (Journal of Neuroscience)
Synaptic cell adhesion molecules are increasingly gaining attention for conferring specific properties to individual synapses. Netrin-G1 and netrin-G2 are trans-synaptic adhesion molecules that distribute on distinct axons, and their presence restricts the expression of their cognate receptors, NGL1 and NGL2, respectively, to specific subdendritic segments of target neurons. However, the neural circuits and functional roles of netrin-G isoform complexes remain unclear. Here, we use netrin-G-KO and NGL-KO mice to reveal that netrin-G1/NGL1 and netrin-G2/NGL2 interactions specify excitatory synapses in independent hippocampal pathways. In the hippocampal CA1 area, netrin-G1/NGL1 and netrin-G2/NGL2 were expressed in the temporoammonic and Schaffer collateral pathways, respectively. The lack of presynaptic netrin-Gs led to the dispersion of NGLs from postsynaptic membranes. In accord, netrin-G mutant synapses displayed opposing phenotypes in long-term and short-term plasticity through discrete biochemical pathways. The plasticity phenotypes in netrin-G-KOs were phenocopied in NGL-KOs, with a corresponding loss of netrin-Gs from presynaptic membranes. Our findings show that netrin-G/NGL interactions differentially control synaptic plasticity in distinct circuits via retrograde signaling mechanisms and explain how synaptic inputs are diversified to control neuronal activity.

Phase transition in the density of states of quantum spin glasses - Erdös, László; Schröder, Dominik J (Mathematical Physics, Analysis and Geometry)
We prove that the empirical density of states of quantum spin glasses on arbitrary graphs converges to a normal distribution as long as the maximal degree is negligible compared with the total number of edges. This extends the recent results of Keating et al. (2014) that were proved for graphs with bounded chromatic number and with symmetric coupling distribution. Furthermore, we generalise the result to arbitrary hypergraphs. We test the optimality of our condition on the maximal degree for p-uniform hypergraphs that correspond to p-spin glass Hamiltonians acting on n distinguishable spin- 1/2 particles. At the critical threshold p = n1/2 we find a sharp classical-quantum phase transition between the normal distribution and the Wigner semicircle law. The former is characteristic to classical systems with commuting variables, while the latter is a signature of noncommutative random matrix theory.

Hypersurfaces and their singularities in partial correlation testing - Lin, Shaowei; Uhler, Caroline; Sturmfels, Bernd; Bühlmann, Peter (Foundations of Computational Mathematics)
An asymptotic theory is developed for computing volumes of regions in the parameter space of a directed Gaussian graphical model that are obtained by bounding partial correlations. We study these volumes using the method of real log canonical thresholds from algebraic geometry. Our analysis involves the computation of the singular loci of correlation hypersurfaces. Statistical applications include the strong-faithfulness assumption for the PC algorithm and the quantification of confounder bias in causal inference. A detailed analysis is presented for trees, bow ties, tripartite graphs, and complete graphs.

Deterministic progenitor behavior and unitary production of neurons in the neocortex - Gao, Peng; Postiglione, Maria P; Krieger, Teresa; Hernandez, Luisirene; Wang, Chao; Han, Zhi; Streicher, Carmen; Papusheva, Ekaterina; Insolera, Ryan; Chugh, Kritika; Kodish, Oren; Huang, Kun; et al. (Cell)
Radial glial progenitors (RGPs) are responsible for producing nearly all neocortical neurons. To gain insight into the patterns of RGP division and neuron production, we quantitatively analyzed excitatory neuron genesis in the mouse neocortex using Mosaic Analysis with Double Markers, which provides single-cell resolution of progenitor division patterns and potential in vivo. We found that RGPs progress through a coherent program in which their proliferative potential diminishes in a predictable manner. Upon entry into the neurogenic phase, individual RGPs produce ∼8–9 neurons distributed in both deep and superficial layers, indicating a unitary output in neuronal production. Removal of OTX1, a transcription factor transiently expressed in RGPs, results in both deep- and superficial-layer neuron loss and a reduction in neuronal unit size. Moreover, ∼1/6 of neurogenic RGPs proceed to produce glia. These results suggest that progenitor behavior and histogenesis in the mammalian neocortex conform to a remarkably orderly and deterministic program.

Existing cardiomyocytes generate cardiomyocytes at a low rate after birth in mice - Ali, Shah; Hippenmeyer, Simon; Saadat, Lily; Luo, Liqun; Weissman, Irving; Ardehali, Reza (PNAS)
The mammalian heart has long been considered a postmitotic organ, implying that the total number of cardiomyocytes is set at birth. Analysis of cell division in the mammalian heart is complicated by cardiomyocyte binucleation shortly after birth, which makes it challenging to interpret traditional assays of cell turnover [Laflamme MA, Murray CE (2011) Nature 473(7347):326–335; Bergmann O, et al. (2009) Science 324(5923):98–102]. An elegant multi-isotope imaging-mass spectrometry technique recently calculated the low, discrete rate of cardiomyocyte generation in mice [Senyo SE, et al. (2013) Nature 493(7432):433–436], yet our cellular-level understanding of postnatal cardiomyogenesis remains limited. Herein, we provide a new line of evidence for the differentiated α-myosin heavy chain-expressing cardiomyocyte as the cell of origin of postnatal cardiomyogenesis using the “mosaic analysis with double markers” mouse model. We show limited, life-long, symmetric division of cardiomyocytes as a rare event that is evident in utero but significantly diminishes after the first month of life in mice; daughter cardiomyocytes divide very seldom, which this study is the first to demonstrate, to our knowledge. Furthermore, ligation of the left anterior descending coronary artery, which causes a myocardial infarction in the mosaic analysis with double-marker mice, did not increase the rate of cardiomyocyte division above the basal level for up to 4 wk after the injury. The clonal analysis described here provides direct evidence of postnatal mammalian cardiomyogenesis.

Dendrite morphogenesis depends on relative levels of NT-3/TrkC signaling - William, Joo; Hippenmeyer, Simon; Luo, Liqun (Science)
Neurotrophins regulate diverse aspects of neuronal development and plasticity, but their precise in vivo functions during neural circuit assembly in the central brain remain unclear. We show that the neurotrophin receptor tropomyosin-related kinase C (TrkC) is required for dendritic growth and branching of mouse cerebellar Purkinje cells. Sparse TrkC knockout reduced dendrite complexity, but global Purkinje cell knockout had no effect. Removal of the TrkC ligand neurotrophin-3 (NT-3) from cerebellar granule cells, which provide major afferent input to developing Purkinje cell dendrites, rescued the dendrite defects caused by sparse TrkC disruption in Purkinje cells. Our data demonstrate that NT-3 from presynaptic neurons (granule cells) is required for TrkC-dependent competitive dendrite morphogenesis in postsynaptic neurons (Purkinje cells)—a previously unknown mechanism of neural circuit development.

Verification of markov decision processes using learning algorithms - Brázdil, Tomáš; Chatterjee, Krishnendu; Chmelik, Martin; Forejt, Vojtěch; Kretinsky, Jan; Kwiatkowska, Marta; Parker, David; Ujma, Mateusz (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We present a general framework for applying machine-learning algorithms to the verification of Markov decision processes (MDPs). The primary goal of these techniques is to improve performance by avoiding an exhaustive exploration of the state space. Our framework focuses on probabilistic reachability, which is a core property for verification, and is illustrated through two distinct instantiations. The first assumes that full knowledge of the MDP is available, and performs a heuristic-driven partial exploration of the model, yielding precise lower and upper bounds on the required probability. The second tackles the case where we may only sample the MDP, and yields probabilistic guarantees, again in terms of both the lower and upper bounds, which provides efficient stopping criteria for the approximation. The latter is the first extension of statistical model checking for unbounded properties inMDPs. In contrast with other related techniques, our approach is not restricted to time-bounded (finite-horizon) or discounted properties, nor does it assume any particular properties of the MDP. We also show how our methods extend to LTL objectives. We present experimental results showing the performance of our framework on several examples.

Nanodomain coupling explains Ca^2+ independence of transmitter release time course at a fast central synapse - Arai, Itaru; Jonas, Peter M (eLife)
A puzzling property of synaptic transmission, originally established at the neuromuscular junction, is that the time course of transmitter release is independent of the extracellular Ca2+ concentration ([Ca2+]o), whereas the rate of release is highly [Ca2+]o-dependent. Here, we examine the time course of release at inhibitory basket cell-Purkinje cell synapses and show that it is independent of [Ca2+]o. Modeling of Ca2+-dependent transmitter release suggests that the invariant time course of release critically depends on tight coupling between Ca2+ channels and release sensors. Experiments with exogenous Ca2+ chelators reveal that channel-sensor coupling at basket cell-Purkinje cell synapses is very tight, with a mean distance of 10–20 nm. Thus, tight channel-sensor coupling provides a mechanistic explanation for the apparent [Ca2+]o independence of the time course of release.

Bifurcation of the endocytic pathway into Rab5-dependent and -independent transport to the vacuole - Toshima, Junko; Nishinoaki, Show; Sato, Yoshifumi; Yamamoto, Wataru; Furukawa, Daiki; Siekhaus, Daria E; Sawaguchi, Akira; Toshima, Jiro (Nature Communications)
The yeast Rab5 homologue, Vps21p, is known to be involved both in the vacuolar protein sorting (VPS) pathway from the trans-Golgi network to the vacuole, and in the endocytic pathway from the plasma membrane to the vacuole. However, the intracellular location at which these two pathways converge remains unclear. In addition, the endocytic pathway is not completely blocked in yeast cells lacking all Rab5 genes, suggesting the existence of an unidentified route that bypasses the Rab5-dependent endocytic pathway. Here we show that convergence of the endocytic and VPS pathways occurs upstream of the requirement for Vps21p in these pathways. We also identify a previously unidentified endocytic pathway mediated by the AP-3 complex. Importantly, the AP-3-mediated pathway appears mostly intact in Rab5-disrupted cells, and thus works as an alternative route to the vacuole/lysosome. We propose that the endocytic traffic branches into two routes to reach the vacuole: a Rab5-dependent VPS pathway and a Rab5-independent AP-3-mediated pathway.

Characterizing spiking in noisy type II neurons - Bodova, Katarina; Paydarfar, David; Forger, Daniel (Journal of Theoretical Biology)
Understanding the dynamics of noisy neurons remains an important challenge in neuroscience. Here, we describe a simple probabilistic model that accurately describes the firing behavior in a large class (type II) of neurons. To demonstrate the usefulness of this model, we show how it accurately predicts the interspike interval (ISI) distributions, bursting patterns and mean firing rates found by: (1) simulations of the classic Hodgkin-Huxley model with channel noise, (2) experimental data from squid giant axon with a noisy input current and (3) experimental data on noisy firing from a neuron within the suprachiasmatic nucleus (SCN). This simple model has 6 parameters, however, in some cases, two of these parameters are coupled and only 5 parameters account for much of the known behavior. From these parameters, many properties of spiking can be found through simple calculation. Thus, we show how the complex effects of noise can be understood through a simple and general probabilistic model.

Rabinizer 3: Safraless translation of ltl to small deterministic automata - Komárková, Zuzana; Kretinsky, Jan (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We present a tool for translating LTL formulae into deterministic ω-automata. It is the first tool that covers the whole LTL that does not use Safra’s determinization or any of its variants. This leads to smaller automata. There are several outputs of the tool: firstly, deterministic Rabin automata, which are the standard input for probabilistic model checking, e.g. for the probabilistic model-checker PRISM; secondly, deterministic generalized Rabin automata, which can also be used for probabilistic model checking and are sometimes by orders of magnitude smaller. We also link our tool to PRISM and show that this leads to a significant speed-up of probabilistic LTL model checking, especially with the generalized Rabin automata.

Validity of spin-wave theory for the quantum Heisenberg model - Correggi, Michele; Giuliani, Alessandro; Seiringer, Robert (EPL)
Spin-wave theory is a key ingredient in our comprehension of quantum spin systems, and is used successfully for understanding a wide range of magnetic phenomena, including magnon condensation and stability of patterns in dipolar systems. Nevertheless, several decades of research failed to establish the validity of spin-wave theory rigorously, even for the simplest models of quantum spins. A rigorous justification of the method for the three-dimensional quantum Heisenberg ferromagnet at low temperatures is presented here. We derive sharp bounds on its free energy by combining a bosonic formulation of the model introduced by Holstein and Primakoff with probabilistic estimates and operator inequalities.

Mind the nuisance: Gaussian process classification using privileged noise - Hernandez Lobato, Daniel; Sharmanska, Viktoriia; Kersting, Kristian; Lampert, Christoph; Quadrianto, Novi (Advances in Neural Information Processing Systems)
The learning with privileged information setting has recently attracted a lot of attention within the machine learning community, as it allows the integration of additional knowledge into the training process of a classifier, even when this comes in the form of a data modality that is not available at test time. Here, we show that privileged information can naturally be treated as noise in the latent function of a Gaussian process classifier (GPC). That is, in contrast to the standard GPC setting, the latent function is not just a nuisance but a feature: it becomes a natural measure of confidence about the training data by modulating the slope of the GPC probit likelihood function. Extensive experiments on public datasets show that the proposed GPC method using privileged noise, called GPC+, improves over a standard GPC without privileged knowledge, and also over the current state-of-the-art SVM-based method, SVM+. Moreover, we show that advanced neural networks and deep learning methods can be compressed as privileged information.

The optogenetic promise for oncology: Episode I - Inglés Prieto, Álvaro; Gschaider-Reichhart, Eva; Schelch, Karin; Janovjak, Harald L; Grusch, Michael (Molecular and Cellular Oncology)
As light-based control of fundamental signaling pathways is becoming a reality, the field of optogenetics is rapidly moving beyond neuroscience. We have recently developed receptor tyrosine kinases that are activated by light and control cell proliferation, epithelial–mesenchymal transition, and angiogenic sprouting—cell behaviors central to cancer progression.

Enhanced chosen-ciphertext security and applications - Dachman Soled, Dana; Fuchsbauer, Georg; Mohassel, Payman; O’Neill, Adam (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We introduce and study a new notion of enhanced chosen-ciphertext security (ECCA) for public-key encryption. Loosely speaking, in the ECCA security experiment, the decryption oracle provided to the adversary is augmented to return not only the output of the decryption algorithm on a queried ciphertext but also of a randomness-recovery algorithm associated to the scheme. Our results mainly concern the case where the randomness-recovery algorithm is efficient. We provide constructions of ECCA-secure encryption from adaptive trapdoor functions as defined by Kiltz et al. (EUROCRYPT 2010), resulting in ECCA encryption from standard number-theoretic assumptions. We then give two applications of ECCA-secure encryption: (1) We use it as a unifying concept in showing equivalence of adaptive trapdoor functions and tag-based adaptive trapdoor functions, resolving an open question of Kiltz et al. (2) We show that ECCA-secure encryption can be used to securely realize an approach to public-key encryption with non-interactive opening (PKENO) originally suggested by Damgård and Thorbek (EUROCRYPT 2007), resulting in new and practical PKENO schemes quite different from those in prior work. Our results demonstrate that ECCA security is of both practical and theoretical interest.

Motif depletion in bacteriophages infecting hosts with CRISPR systems - Kupczok, Anne; Bollback, Jonathan P (BMC Genomics)
Background: CRISPR is a microbial immune system likely to be involved in host-parasite coevolution. It functions using target sequences encoded by the bacterial genome, which interfere with invading nucleic acids using a homology-dependent system. The system also requires protospacer associated motifs (PAMs), short motifs close to the target sequence that are required for interference in CRISPR types I and II. Here, we investigate whether PAMs are depleted in phage genomes due to selection pressure to escape recognition.Results: To this end, we analyzed two data sets. Phages infecting all bacterial hosts were analyzed first, followed by a detailed analysis of phages infecting the genus Streptococcus, where PAMs are best understood. We use two different measures of motif underrepresentation that control for codon bias and the frequency of submotifs. We compare phages infecting species with a particular CRISPR type to those infecting species without that type. Since only known PAMs were investigated, the analysis is restricted to CRISPR types I-C and I-E and in Streptococcus to types I-C and II. We found evidence for PAM depletion in Streptococcus phages infecting hosts with CRISPR type I-C, in Vibrio phages infecting hosts with CRISPR type I-E and in Streptococcus thermopilus phages infecting hosts with type II-A, known as CRISPR3.Conclusions: The observed motif depletion in phages with hosts having CRISPR can be attributed to selection rather than to mutational bias, as mutational bias should affect the phages of all hosts. This observation implies that the CRISPR system has been efficient in the groups discussed here.

Distributed computation of persistent homology - Bauer, Ulrich; Kerber, Michael; Reininghaus, Jan (Proceedings of the Workshop on Algorithm Engineering and Experiments)
Persistent homology is a popular and powerful tool for capturing topological features of data. Advances in algorithms for computing persistent homology have reduced the computation time drastically – as long as the algorithm does not exhaust the available memory. Following up on a recently presented parallel method for persistence computation on shared memory systems [1], we demonstrate that a simple adaption of the standard reduction algorithm leads to a variant for distributed systems. Our algorithmic design ensures that the data is distributed over the nodes without redundancy; this permits the computation of much larger instances than on a single machine. Moreover, we observe that the parallelism at least compensates for the overhead caused by communication between nodes, and often even speeds up the computation compared to sequential and even parallel shared memory algorithms. In our experiments, we were able to compute the persistent homology of filtrations with more than a billion (109) elements within seconds on a cluster with 32 nodes using less than 6GB of memory per node.

Structure, function and plasticity of hippocampal dentate gyrus microcircuits - Jonas, Peter M; Lisman, John (Frontiers in Neural Circuits)
The hippocampus mediates several higher brain functions, such as learning, memory, and spatial coding. The input region of the hippocampus, the dentate gyrus, plays a critical role in these processes. Several lines of evidence suggest that the dentate gyrus acts as a preprocessor of incoming information, preparing it for subsequent processing in CA3. For example, the dentate gyrus converts input from the entorhinal cortex, where cells have multiple spatial fields, into the spatially more specific place cell activity characteristic of the CA3 region. Furthermore, the dentate gyrus is involved in pattern separation, transforming relatively similar input patterns into substantially different output patterns. Finally, the dentate gyrus produces a very sparse coding scheme in which only a very small fraction of neurons are active at any one time.

Clear and Compress: Computing Persistent Homology in Chunks - Bauer, Ulrich; Kerber, Michael; Reininghaus, Jan (Topological Methods in Data Analysis and Visualization III)
We present a parallel algorithm for computing the persistent homology of a filtered chain complex. Our approach differs from the commonly used reduction algorithm by first computing persistence pairs within local chunks, then simplifying the unpaired columns, and finally applying standard reduction on the simplified matrix. The approach generalizes a technique by Günther et al., which uses discrete Morse Theory to compute persistence; we derive the same worst-case complexity bound in a more general context. The algorithm employs several practical optimization techniques, which are of independent interest. Our sequential implementation of the algorithm is competitive with state-of-the-art methods, and we further improve the performance through parallel computation.